(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Dr. Triguna Sen was a well-known educationist, political activist, and social worker, Above all, he was a successor to the National Education Movement, One of the main objectives of the movement was education in the mother tongue. He was born in Assam, on December 24, 1905. He received a degree in mechanical engineering from the Bengal Technical Institute (BTI) under the National Council of education, Bengal in 1926 and a doctorate from the Technical University of Munich in 1933. He jumped into India’s freedom struggle while still a student. His association with revolutionary groups like Anushilan Samiti and Jugantar Dal easily brought him to the attention of the British government, which resulted in his imprisonment and expulsion from Bengal. Dr. Sen spent a large part of his life in Jadavpur, during which time he played a significant role in transforming the College of Engineering and Technology (CET) into a full-fledged university. Dr. Sen made the university that pioneers of the national education movement, including Satish Chandra, dream of a reality. He then served in Smt. Indira Gandhi’s cabinet, first as the Minister of Education and later as the Minister of Petroleum and Chemicals—above all, his important contribution to the formulation of the National Education Policy of 1968 is well known. As Minister of Petroleum and Chemicals, he tackled the question of nationalization of the oil and pharmaceutical industries. He was devoted to the independent language and identity of the Bengalis. Therefore, he played a leading role in the Bangladesh independence movement in 1971. Additionally, he enjoyed Bengali literature and culture and funded numerous institutions and cultural endeavors. He worked for the development of education until the end of his life. In the present article, through a discussion of his life, we will try to understand how the continuity of the education movement played a leading role in the development of the country’s educational infrastructure.